2003
DOI: 10.1001/archotol.129.6.623
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Laser Surgery for Early Glottic Cancers

Abstract: Transoral laser surgery is an oncologically safe, function-preserving modality for treatment of early glottic cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 31 publications
4
41
1
1
Order By: Relevance
“…This contrary local recurrence trend may represent limitations in the current clinical staging systems to account for the local aggressiveness of glottic SCC. Additional studies evaluating endoscopic cordectomy of have reported similar oncologic success rates comparative with the present study [1,2]. Although oncologic outcomes are poorer in SCC with AC-involvement as compared with SCC without AC-involvement, CO 2 laser cordectomy continues to demonstrate excellent local control and laryngeal preservation rates as compared with the other therapeutic options of radiation therapy [16] and open surgery [15,17].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This contrary local recurrence trend may represent limitations in the current clinical staging systems to account for the local aggressiveness of glottic SCC. Additional studies evaluating endoscopic cordectomy of have reported similar oncologic success rates comparative with the present study [1,2]. Although oncologic outcomes are poorer in SCC with AC-involvement as compared with SCC without AC-involvement, CO 2 laser cordectomy continues to demonstrate excellent local control and laryngeal preservation rates as compared with the other therapeutic options of radiation therapy [16] and open surgery [15,17].…”
Section: Discussionsupporting
confidence: 72%
“…While the pathophysiologic basis for the increased aggressiveness of this laryngeal cancer subsite requires further study, the published clinical experience regarding the treatment outcomes for SCC involving the AC is limited. In particular, the published endoscopic CO 2 laser cordectomy experience to date has typically reported either oncologic outcomes [1][2][3] or voice outcomes with quality of life descriptions [4]. However, when evaluating the treatment recommendations for AC carcinomas consideration of both oncologic and voice outcomes is required and little is currently known regarding the oncologic and voice outcomes within a single patient cohort [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, local control rates for radiotherapy are reported between 78% and 94% 10,15,16 and for CO 2 laser surgery between 77% and 95%. 4,[8][9][10]17 Our 5-year local control rates are somewhat lower than the local control rates found in the literature. A possible explanation might be that other authors reported a 3-year local control rate and included Tis carcinomas in their group.…”
Section: Figurecontrasting
confidence: 81%
“…A possible explanation might be that other authors reported a 3-year local control rate and included Tis carcinomas in their group. 4,8,17 In the current study, we showed that patients with T1a glottic laryngeal carcinoma treated primarily with CO 2 laser surgery had a significantly better 5-year laryngeal preservation rate (95%) than patients treated with radiotherapy (77%), despite the lack of difference in local control. For the CO 2 laser group, our 5-year laryngeal preservation rate is in concordance with previously published results.…”
Section: Figurementioning
confidence: 46%
See 1 more Smart Citation